P3.159 Identifying Syphilis Risk Networks Through Venue Attendance in San Francisco. (13th July 2013) - Stephens, S; Fann, C; Strona, F; Wolf, W; Cohen, S; Philip, S; Bernstein, K
Abstract : Background: Many men who have sex with men (MSM) interviewed through syphilis partner services report large numbers of sex partners but can provide contact information for relatively few. Prioritizing interventions for patients with syphilis who are part of large sexual networks may be "high yield" and identifying venues named by syphilis cases who report high numbers of partners may help identify such networks. We compared syphilis patients across three levels of sexual partner frequency. Methods: For each venue reported by interviewed patients with early syphilis in 2011, we examined the distribution of total reported sex partners (not only named partners) in the last year. Based on the median number of total partners among men who named each venue, we categorised venues into three levels of partner frequency: high (> 15 partners reported), medium (6–15 partners reported), and low (< 6 partners reported). Interviewed early syphilis cases were then classified as attending high, medium, or low partner frequency venues; sociodemographic and risk behaviours were compared across the three venue categories using X 2 tests. Results: In 2011, 433 patients with early syphilis named 32 venues. One hundred forty three (32.3%) patients were categorised as high partner frequency venue users, 226 (51.0%) as medium partner frequency venue users, and 74 (16.7%) as low partner frequency-only venue users. Patients with early syphilis that reported meeting partners at high-frequency venues were generally older, more likely to be white, have a previous syphilis infection, use methamphetamines in the previous year, and be HIV-infected (all p < 0.05) than those who reported meeting partners at medium-frequency and low-frequency venues. Discussion: Venues where partners are met may be an appropriate proxy for network membership. Targeting additional resources, outreach, and services to clients who attend high frequency venues may have a positive impact on syphilis prevention efforts.